Optical Fiber Bragg Grating-Based Measurement of Fluid-Structure Interaction on a Cantilever Panel in High-Speed Flow - Luke Pollock; Harald Kleine; Andrew Neely; Graham Wild (IEEE Access, 2024)
Optical fiber Bragg grating (FBG) technology offers many advantages over conventional electrical sensors for the measurement of fluid-structure interaction (FSI). In this work, FBGs are used to measure the dynamic response of 3 mm, 2 mm, and 1 mm thick aluminum cantilever panels under the influence of Mach 2 reflected shock impingement in the UNSW Canberra supersonic blowdown facility. Results compared during start-up and steady-state with high-speed digital video schlieren and laser Doppler vibrometry indicate that FBGs can successfully capture the temporal and spectral characteristics of high-speed FSI. The torsional mode of the 1 mm plate is spectrally captured by the FBG with only a single sensor. Furthermore, it is shown that error in the FBG signal is comparable to that of a laser Doppler vibrometer. The greatest challenge remains the efficient decoupling of thermal effects.